An Analysis of Application of Multiple Comparison Tests (Post-Hoc) In ANOVA In Recently Published Medical Research Literature - Patel, Swati; Naik, Vipin; Patel, Prakash (National Journal of Community Medicine, 2015)
Background: The usage of statistical methods specially ANOVA and post hoc test are increase in medical research, however inaccurate application of ANOVA and post hoc test were observed commonly. So we reviewed application of ANOVA and post-hoc test in recent published biomedical research literature. Method: Original articles published in bio-medical journals subscribed by the central library of our institute (SMIMER, Surat) were reviewed for statistical applications mainly ANOVA and post hoc test. Result: Among the 1128 reviewed articles 800 (70.92%) used inferential statistical techniques. Among these 203 (25.37) articles were used ANOVA and out of that 92 (45.23%) were used post hoc test. Maximum usage of post hoc test was found in basic and paramedical research article, whereas least usage was found in the surgical articles. It has been also observed that out of the 92 original articles which applied post hoc test, in 28 (30.43%) the application was inappropriate. Conclusion: Conceptual understanding and application of ANOVA and Post hoc test was lacking among bio-medical researcher.